SOLUTIONS TO HOUSING PROBLEMS FOR LOW-INCOME PEOPLE IN HO CHI MINH CITY - NGUYEN THI BICH LOAN (Köz-gazdaság, 2020)
The process of globalization has created golden opportunities for the economies of developing countries to keep up with other countries. However, besides the positive effects, globalization has raised many implications; one of these emerging issues is the immigration process into big cities due to high demand of labor forces along with the process of urbanization at breakneck speed. Therefore, meeting the housing needs in the urban areas of the low income strata had become the new challenge for developing cities. This article refers to the solutions to housing problems for low-income people in Ho Chi Minh City.